2019
DOI: 10.1136/neurintsurg-2018-014631
|View full text |Cite
|
Sign up to set email alerts
|

A2, M2, P2 aneurysms and beyond: results of treatment with pipeline embolization device in 65 patients

Abstract: BackgroundIntracranial aneurysms located in the distal vessels are rare and remain a challenge to treat through surgical or endovascular interventions.ObjectiveTo describe a multicenter approach with flow diversion using the pipeline embolization device (PED) for treatment of distal intracranial aneurysms.MethodsCases of distal intracranial aneurysms defined as starting on or beyond the A2 anterior cerebral artery, M2 middle cerebral artery, and P2 posterior cerebral artery segments were included in the final … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 13 publications
0
22
1
Order By: Relevance
“…8,16-19 Perforators are usually kept patent by a “sump” effect; however, acute or late symptomatic or asymptomatic perforator stroke is reported. 6,17-19 In the Saleme et al 18 series, permanent neurological deficits occurred in 9.4% of patients during hospitalization and transient events occurred in 17.4% of cases in the 6-mo period. Careful dual antiplatelet therapy and use of a single slightly oversized FDD, to reduce metal coverage, might be useful to decrease the risk of perforators occlusion.…”
Section: Bifurcation Aneurysmsmentioning
confidence: 96%
See 1 more Smart Citation
“…8,16-19 Perforators are usually kept patent by a “sump” effect; however, acute or late symptomatic or asymptomatic perforator stroke is reported. 6,17-19 In the Saleme et al 18 series, permanent neurological deficits occurred in 9.4% of patients during hospitalization and transient events occurred in 17.4% of cases in the 6-mo period. Careful dual antiplatelet therapy and use of a single slightly oversized FDD, to reduce metal coverage, might be useful to decrease the risk of perforators occlusion.…”
Section: Bifurcation Aneurysmsmentioning
confidence: 96%
“…The occlusion rate was 83% (mean follow-up time: 6 mo). 6 In two series of distal vessel aneurysms treated with the FRED Jr or the PED complete/near complete, occlusion rate was 78%. The rate of ischemic events varied from 7% to 17.4%.…”
Section: Distal Aneurysmsmentioning
confidence: 97%
“…A multicohort study from 3 centers involving 46 patients and 46 distal aneurysms, the use of the PED or FRED resulted in nearly 80% rate of complete or near-complete occlusion after a mean follow-up of 13 months with a complications rate of 4.3% resulting form 2 cases of perforator ischemia (Ravindran et al, 2018 ). A recent multicenter analysis of a relatively large cohort of distal aneurysms involving the second segments of the anterior, middle and posterior cerebral arteries demonstrated a high efficacy rate of flow diversion in these distal and challenging configuration (Primiani et al, 2019 ). The authors reported a procedural complication rate of 7.7% and 95% rate of good clinical outcome among 60 patients with available clinical follow-ups.…”
Section: Discussionmentioning
confidence: 99%
“…MCA proximal and distal aneurysms are relatively rare, and most previous studies of proximal and distal aneurysms focus on the selection of treatment options for aneurysm rupture. Few studies exist on the relationship between MCA geometry and the formation of proximal and distal aneurysms [24][25][26][27]. To the best of our knowledge, the relation of both the α and β to the formation of proximal and distal MCA aneurysms has not yet been reported.…”
Section: Morphological Features Between Mca Proximal and Distal Aneurmentioning
confidence: 99%